Ceftaroline in Combination With Trimethoprim-Sulfamethoxazole for Salvage Therapy of Methicillin-Resistant Staphylococcus aureus Bacteremia and Endocarditis. (8th July 2014) - Fabre, Valeria; Ferrada, Marcela; Buckel, Whitney R.; Avdic, Edina; Cosgrove, Sara E.
Abstract: No clinical trials have investigated the use of ceftaroline fosamil for salvage therapy of methicillin-resistant Staphylococcus aureus bacteremia and endocarditis. We report data on 29 patients who received ceftaroline ± another antimicrobial for this indication. Ninety percent of patients had microbiologic cure and 31% had treatment success with a median follow-up of 6 months.